Production of Tagatose by Whole-cell Bioconversion from Fructose Using Corynebacterium glutamicum - Jeon, Eun Jung; Lee, Young-Mi; Choi, Eun Jung; Kim, Seong-Bo; Jeong, Ki Jun (Biotechnology and bioprocess engineering, 2023)
s Tagatose is a rarely occurring sugar found in food and sweet fruits. It is a potential sweetener with low calories but a sweetness similar to that of sucrose. In this study, we developed a whole-cell biocatalyst using Corynebacterium glutamicum for direct bioconversion of fructose to tagatose. First, we constructed a biological conversion pathway for the conversion of fructose to tagatose by expressing tagatose 4-epimerase (TN) from Thermotoga neapolitana in C. glutamicum. Next, to increase the expression level of the enzyme, we engineered copy number of plasmid. Plasmid library was constructed by randomizing the cgrI antisense RNA region in the plasmid, and the plasmid with high-copy number was isolated using fluorescence-activated single cell sorting (FACS)-based high-throughput screening. The isolated plasmid, pHCP7, had 2-fold higher copy numbers than the original plasmid. A higher expression level and conversion yield could be achieved using pHCP7. Finally, we examined a novel tagatose 4-epimerase TN(KNF4E) isolated from Kosmotoga olearia. The gene expression level was further increased (33.9% of total fraction) through codon optimization and expression in pHCP7, and a conversion yield as high as 21.7% was achieved.